Vibrations Caused By Train Passages In Underground Tunnel Compared To Vibrations From Ground Surface Transportation – Some Results Of Investigations - Stypuła Krzysztof (Archives of Civil Engineering, 2014)
The paper describes experimental investigations of vibrations caused by train passages in the shallow underground tunnel (in Warsaw, Poland) in comparison to the results of measurements of vibrations from ground surface transportation (trams and buses). Propagation of surface ground vibrations from underground tunnel is presented. The problem of dynamic response of a building and influence of vibrations caused by underground on people residing in a building is discussed as well. The dynamic response of the building to underground vibrations is essentially different from the response of a building excited by surface sources of transport vibrations. Also the distribution of influence of the transport vibrations on people in the building is significantly different in both cases.